Mapping of QTLs for Resistance to Late Wilt of Maize in Egypt Using SNPs - Al Taweel, Hamed Muhammad (AUC Knowledge Fountain, 2013)
Late Wilt disease in maize, caused by Cephalosporium maydis, is considered to be the most economically important fungal disease of maize in Egypt. The fungus is a soil borne vascular disease that affects vascular tissue by penetrating the root system and colonizing the xylem. An infection rate of up to 100% can be recorded in fields of susceptible hybrids, which can result in a yield loss of 50%. Therefore, characterizing traits and their genes that confer resistance against C. maydis is a priority in maize crop management. In this study, quantitative trait loci (QTL) of late wilt resistance were mapped by using eight F3 populations encompassing 554 lines ( five populations belongs to the stiff stalk group, while the other three belongs to the non-stiff stalk genetic group) resulting from crossings between five resistant and six susceptible inbred lines. The populations and their parents were evaluated under artificial infestation using the four Egyptian clonal lineages of the pathogen during the growing season in 2011. Variation shown in infection incidence within the populations was significant regarding disease symptoms. Parents for each of the 8 population showed high diversion in infection incidence, varied between 5% for resistant parents, while reached average of 66% for susceptible parents. QTLs were mapped on the public linkage map IBM2 constructed with 842 SNPs. Composite Interval Mapping on IBM2 linkage map identified major QTLs accounting for 1 to 58 % of the phenotypic variance, which can be candidate markers used in Marker Assisted Selection to breed for late wilt resistance in maize.